ФИЛОСОФИЯЛЫҚ ТӘРБИЯ ҲӘМ ШАХСТЫҢ ҚӘЛИПЛЕСИЎИ - Усенов, Ж.; Назарбаев, М. (FAN va JAMIYAT, 2021)
The article defines new tasks of philosophical education and its formation in the personality. There is also an opinion about the relevance of education, its features and relationship with other disciplines. The importance of aesthetic, pedagogical and religious education in human education is emphasized.